Performance Analysis of Dijkstra-Based Weighted Sum Minimization Routing Algorithm for Wireless Mesh Networks - Nuha A. S. Alwan (Modelling and Simulation in Engineering)
Multiobjective optimization methods for routing in static wireless mesh networks (WMNs), with more than one QoS measure to be optimized, are highly challenging. To optimize the performance for a given end-to-end route in a static network, the most common metrics that need to be optimized or bounded are the path capacity and the end-to-end delay. In this work, we focus on combining desirable properties of these two metrics by minimizing a weighted metrics sum via a Dijkstra-based algorithm. The approach is directed towards fast convergence rather than optimality. It is shown that the resulting algorithm provides more satisfactory results than simple Dijkstra-based pruning algorithms in terms of simultaneously achieving high capacity and small delay. The effect of changing the weighting factor on the proposed algorithm performance is investigated.